Implemetasi Algoritma Apriori dalam Penjualan Mebel - Desyanti; Dewi Anjani; Desi Novianti (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
CV. Andalas Jaya Furniture Dumai is a company engaged in the sale of furniture. Which every month CV. Andalas Jaya Furniture Dumai performs tens to hundreds of sales transactions. Currently CV. Andalas Jaya Furniture Dumai needs a strategy to increase sales, because there are many stocks of goods in the warehouse that have piled up and have not been sold, resulting in a stagnation of capital turnover. For that we need an analysis that can help CV. Andalas Jaya Furniture Dumai in managing which goods must be stocked according to consumer needs. There are several algorithms used to perform Market Basket Analysis, one of which is the Apriori algorithm. In this study, researchers will use the a priori algorithm to classify data on sales of CV. Andalas Jaya Furniture Dumai based on their tendency to appear together in a transaction. The results of this study are if a consumer buys an AC then he has a 71.42% chance of buying a TV and if he buys a TV then he has a 31.25% chance of buying an AC, if a consumer buys a TV table then he has a 62.5% chance of buying a TV and if If you buy a TV, you have a 31.25% chance of buying a TV table, if a consumer buys a refrigerator, you have a 100% chance of buying a TV, and if you buy a TV, you have a 31.25% chance of buying a refrigerator. Meanwhile, 25% of the 20 existing transactions contain both of these items